ESTIMASI KEPADATAN ORANGUTAN SUMATERA (Pongo abelii) BERDASARKAN JUMLAH SARANG DI DESA SEKITAR CAGAR ALAM DOLOK SIBUAL-BUALI - Gabriella Junike Maria Azalia Simanjuntak; Pindi Patana; Erni Jumilaty (Peronema Forestry Science Journal, 2015)
Sumatran Orangutan (Pongo abelii) is protected mammal species which existence is now in critically endangered species category of the International Union for Conservation of Nature (IUCN). It’s facing a very high risk of extinction in the wild. This research aimed to estimate Sumatran orangutan density, determined the types of dominant vegetation used as nesting tree, assest the value and Importance Value Index (IVI) of trees located in the village of Aek Nabara. This indirect method was used by counting the number of nests due to the difficulties in finding Sumatran Orangutans in wild habitat. The area of village is  in the border of Dolok Sibual-buali Natural Reserve, South Tapanuli.   The results of this study indicated orangutan population density was 0,006 individuals/km2 or 5,994 individuals/10 ha with the total number of 18 nests. Generally the nest was found at 6-10 meters of tree hight with a sum of 8 nests (44,44%). The highest of Important Value Index (IVI) was Hoteng species (Quercus gamelliflora Blume.). The trees which mostly used by orangutans as a nest was Hau Dolok tree (35,29%).Keywords: Sumatran Orangutan, Orangutan Density, orang utan nest, Important Value Index, Dolok Sibualbuali Natural Reserve